Box-Behnken design based optimization of phenolic extractions from Polygonum equisetiforme roots linked to its antioxidant and antibacterial efficiencies - Elgudayem, Farah; Aldiyab, Abdullah; Albalawi, Marzough Aziz; Omran, Awatif; Kafkas, Nesibe Ebru; Saghrouchni, Hamza; Var, Işil; Rahman, Md Atikur; El Sabagh, Ayman; Sakran, Mohamed; Ben Ahmed, Chedlia (Frontiers in Sustainable Food Systems, 2023)
Purpose The Polygonum equisetifome is a prospective plant source of high protein, unsaturated fatty acids, and useful safe bioactive molecules. Therefore, the aim of this study was to optimize the ultrasonic aqueous extraction of phenols from P. equisetifome roots using Box-Behnken design based statistical modeling, and to evaluate the antioxidant and antibacterial efficiencies of P. equisetifome root extracts against pathogenic bacteria. Methods In this study, the box-behnken design was used to optimize the extraction of phenols. The extraction temperature (30–70°C), ultrasound assisted extraction (UAE) time (1–9 min), and liquid-solid ratio (35–45 mL/g) were investigated as the factors that influence the phenolic yield (Y1) and their DPPH (1,1-diphenyl-2-picrylhydrazyl) scavenging activity (Y2). Results The optimal conditions for both responses were 50°C, 5 min, and 40 mL/g. At these conditions, Y1 reached its maximum to be 45.321 mg GAE/g dry weight and Y2 to be 120.354 μmol Trolox/g dry weight. The P. equisetifome roots contained water soluble phenol, high anthocyanin, and condensed tannins. Interestingly, the P. equisetifome extracts showed a relation to its antioxidant and antibacterial activities, FRAP (Ferric-reducing/antioxidant power), and ABTS scavenging activity were determined. The morphological and physico-chemical features of the extract were analyzed using SEM-EDX, FT-IR, and minimum inhibitory concentration (MIC) was analyzed against several pathogenic bacteria. The antibacterial activity of the extract showed that the extract is more efficient against Staphylococcus aureus, while the P. equisetifome extracts showed efficient MIC against S. aureus, followed by Bacillus cereus. Suggestions The relation of P. equisetifome extracts to its antioxidant, and antibacterial efficiencies open a new avenue of their potential uses in the food and pharmaceutical industries.